Work motivation among Malaysian occupational therapists / Nur Shafiqa Amran and Rosilah Wahab - Amran, Nur Shafiqa; Wahab, Rosilah (Faculty of Health Sciences, Universiti Teknologi MARA, 2024)
Work motivation is an individual's willingness to exert effort towards achieving organizational goals while fulfilling personal needs. Acknowledging that low motivation among health professionals poses challenges to healthcare systems. This research aims to assess the level of work motivation among Malaysian occupational therapists, its types and their relationship with demographic variables. Employing a cross-sectional quantitative design, data were collected from 354 respondents through an online survey using the adapted Work Extrinsic and Intrinsic Motivation Scale (WEIMS). Descriptive and inferential analyses were conducted using Statistical Package for the Social Sciences Version 26 to evaluate the levels and types of work motivation and their association with demographic factors. The findings revealed that a substantial majority of respondents 77.4% exhibited a non-self-determined motivation profile, indicating reliance on external factors for motivation, while only 22.6% had self-determined motivation. The average work motivation score was low (1.23, SD=0.418). Significant differences in motivation were also found based on age, gender, and income. The study concluded that Malaysian occupational therapists have a low level of self-determined work motivation, indicating a preference for more controlled forms. This suggests that most occupational therapists are primarily motivated by external factors rather than intrinsic enjoyment or personal fulfillment in their work.